INTERNALISASI SEMANGAT NASIONALISME MELALUI PENDEKATAN HABITUASI (Perspektif Filsafat Pendidikan) - Anwar, Chairul (Analisis: Jurnal Studi Keislaman, 2014)
INTERNALIZATION  OF THE SPIRIT OF NATIONALISM THROUGH HABITUATION  APPROACH.  (PHILOSOPHY  OF EDUCATION  PERSPECTIVE):  Nationalism  in Indonesia  was born when the people of the country was under the Dutch colonial rule. This ideology appears to be a collective consciousness triggered by feelings of kinship in the past and in the time being, and more importantly,  is united by the same goal for the future. In its development, however, the spirit of nationalism  among the younger generation  seem to weaken. This phenomenon indicates that the role of educational  institutions  are very important  - not only to make the students  understand  and grasp the meaning of nationalism  but  also to  impress  them  the  philosophical  values behind  it.  One  way  that  can  be taken  to  instill  the  values  of nationalism  is through  the approach of habituation    in schools, so that the values of nationalism  embedded in the psyche of the student. By using the  approach,  teachers are believed to be able to instill the values of nationalism to their students either through routine activities, spontaneous activities, awarding exemplary activities,  or, even,  programmed activities.